Trofinetide—a new chapter in rett syndrome’s treatment - Furqan, Muhammad (Frontiers in Pharmacology, 2023)
Trofinetide is the first drug approved by the FDA to treat Rett Syndrome in children aged 2 years or above. The drug significantly improved Rett syndrome behavioral scores Rett syndrome behavioral questionnaire in clinical studies. Although further research is needed to assess potential adverse events, Trofinetide’s notable efficacy signifies a significant advancement in Rett syndrome treatment, offering a new therapeutic avenue with the potential to ameliorate the condition.